Apology - Plato, 428? BCE-348? BCE; Jowett, Benjamin, 1817-1893 (Salt Lake City, UT : Project Gutenberg, 1999)
"Apology" by Plato is a Socratic dialogue written after 399 BC. It presents Socrates's legal defense at his trial, where he faced charges of corrupting Athens's youth and introducing new gods. Standing before a jury of perhaps 500 Athenian men, Socrates refuses to use sophisticated rhetoric, speaking instead in his characteristic questioning style. Rather than compromise his integrity to avoid death, he challenges his accusers and maintains his philosophical principles, insisting his only wisdom comes from knowing that he knows nothing. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Apology_(Plato)
Death of Socrates 1
Release date is 1999-02-01
Produced by Sue Asscher, and David Widger
Keywords: Classical literature; Socrates, 470 BC-399 BC; Philosophy, Ancient